Phyto-synthesized silver nanoparticles from Sargassum subrepandum: anticancer, antimicrobial, and molluscicidal activities - El-Sayed, Heba; Abdelsalam, Asmaa; Morad, Mostafa Y.; Sonbol, Hana; Ibrahim, Amina M.; Tawfik, Eman (Frontiers in Plant Science, 2024)
In the realm of nanotechnology, the use of algae to produce nanoparticles is an environmentally friendly, sustainable, and economically viable strategy. In the present study, the brown macroalgae Sargassum subrepandum was utilized to effectively produce silver nanoparticles (AgNPs). Through various characterization techniques, the AgNPs' structural integrity was confirmed. AgNPs exhibited significant antimicrobial activity against Pseudomonas aeruginosa and Fusarium equiseti.. AgNPs showed cytotoxic effects on the MCF-7 breast adenocarcinoma cell line with an IC50 of 12.5 µg/ml. Treatment with AgNPs resulted in a marked reduction in cell viability, alongside evident apoptotic and necrotic morphological changes in the cancer cells.. Through molecular docking studies, a deeper understanding of the interaction between AgNPs and crucial proteins related to cancer has been achieved,... AgNPs showed a promising molluscicidal action on Biomphalaria alexandrina snails, a Schistosoma mansoni intermediate host. The half-lethal dose (LC50) of AgNPs was determined to be 0.84 mg/L. The potential consequences of its administration include potential disruptions to the glycolysis profile, as well as potential impacts on the steroidal hormone’s estrogen and testosterone and certain kidney function tests. This study highlights the diverse uses of algae-synthesized AgNPs, ranging from healthcare to environmental management, demonstrating their importance in advancing nano-biotechnological solutions.